Response to intranasal steroids in a child with snoring - Voona, Murali Mohan; Iragamreddy, Venugopal Reddy; M., Prabhu; M., Rajesh Babu (International Journal of Contemporary Pediatrics, 2023)
Background: Snoring is a common symptom of underlying conditions, such as allergic rhinitis, Aden tonsillar hypertrophy, or obstructive sleep apnea. It is important to take it into account and examine the situation to prevent the development of severe OSA and its related co-morbidities. Intranasal steroids aid in lowering airway inflammation, which lowers upper airway resistance while you sleep. Early steroid intervention aids in the development of OSA from habitual snoring, but delayed diagnosis is associated with higher OSA recurrence. Methods: Parents of children with snoring aged 4-15 were given a questionnaire and asked if they were willing to pursue treatment. The questionnaire included the patient’s history of snoring, breathing abnormalities, symptoms of mouth breathing, and daytime tiredness. The mother and child started using intranasal fluticasone spray twice daily for six weeks. Results: The study examined 40 individuals between November 2008 and February 2010, with 65% of the participants being men and 35% being women. The age distribution of the study group was 21 kids aged 4 to 7, with 12 children aged 8-11 making up 30% and 7 children aged 12-15 making up 17.5%. The average age was 8.3 years. Intranasal steroids were effective in treating AR symptoms, but some kids had a high likelihood of treatment failure. Allergic symptoms can be prevented by avoiding allergens, and medical anti-allergic medication is essential for reducing nasal and OSA symptoms. Conclusions: Older age and prevalence of AR symptoms are linked risk factors for intranasal Steroid treatment failure in older children.